A comparison of global agricultural monitoring systems and current gaps. (January 2019) - Fritz, Steffen; See, Linda; Bayas, Juan Carlos Laso; Waldner, François; Jacques, Damien; Becker-Reshef, Inbal; Whitcraft, Alyssa; Baruth, Bettina; Bonifacio, Rogerio; Crutchfield, Jim; Rembold, Felix; Rojas, Oscar; et al.
Abstract: Global and regional scale agricultural monitoring systems aim to provide up-to-date information regarding food production to different actors and decision makers in support of global and national food security. To help reduce price volatility of the kind experienced between 2007 and 2011, a global system of agricultural monitoring systems is needed to ensure the coordinated flow of information in a timely manner for early warning purposes. A number of systems now exist that fill this role. This paper provides an overview of the eight main global and regional scale agricultural monitoring systems currently in operation and compares them based on the input data and models used, the outputs produced and other characteristics such as the role of the analyst, their interaction with other systems and the geographical scale at which they operate. Despite improvements in access to high resolution satellite imagery over the last decade and the use of numerous remote-sensing based products by the different systems, there are still fundamental gaps. Based on a questionnaire, discussions with the system experts and the literature, we present the main gaps in the data and in the methods. Finally, we propose some recommendations for addressing these gaps through ongoing improvements in remote sensing, harnessing new and innovative data streams and the continued sharing of more and more data. Highlights: Eight global and regional agricultural monitoring systems are compared Gaps in data are described, where cropland maps, crop calendars and meteorological data are viewed as the most critical Gaps in methods include the need for better predictions of yield and crop production and how to operationalize research methods New sources of remote sensing data, greater data sharing and new sources of information, e.g. from mobile phones, will all help to improve agricultural monitoring